WELFARE OF LAYING HENS IN DIFFERENT DENSITIES OF HOUSING - Castilho, V.A.R.; Garcia, R.G.; Lima, N.D.S.; Nunes, K.C.; Caldara, F.R.; Nääs, I.A.; Barreto, B.; Jacob, F.G. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The study was carried with objective to evaluate the physiologic parameters of bird laying housed on different housing density and period. Were used 150 Dekalb White bird laying with 20 weeks of age was housed on conventional aviary with metallic cages with two subdivision of 50x45x40 cm² and distribution on three treatments: 8 bird laying by cage (562,5 cm²/bird); 10 bird laying by cage (450 cm²/bird) and 12 bird laying by cage (375 cm²/bird), with five repetition each. Were evaluated physiologic parameters (respiratory frequency, cloacal temperature and superficial temperature) and ambience (environmental temperature and relative humidity) during three circles of 28 days. Was adopted a randomized design with factorial arrangement 3x3 (three housing density and three periods). The results demonstrate that the housing density not impaired the respiratory frequency and superficial temperature, however the cloacal temperature differed significantly, being higher at four p.m. and the housing density with 10 bird/cage remained intermediary with others density. The parameters aimed at achieving thermal comfort showed that at the hottest times of the day (until 16:00), regardless of the density, the birds showed higher temperatures in the morning.